COMMUNICATION BARRIERS IN INTERCULTURAL COMMUNICATION AND WAYS TO OVERCOME THEM - Yuldasheva T.A. (European Science Publishing, 2024)
The article examines the problems of intercultural communication associated with the presence of communication barriers. The main types of barriers and ways to overcome them are described. The causes of barriers and the importance of eliminating them for effective communication are analyzed.
Keywords: intercultural communication, communication barriers, language barrier, cultural barrier, psychological barrier, overcoming barriers.